Rekontekstualisasi Tradisi Mamogang: Resistensi Budaya Lokal dan Negosiasi Identitas Keislaman dalam Menyambut Ramadhan di Tapanuli Tengah - Nurhanipah Harahap; Nurhasanah Harahap; Siti Ramadhani; Sakinah Sakinah (Tamadduna: Jurnal Peradaban, 2026)
The Mamogang tradition is a form of local wisdom of the Central Tapanuli community, North Sumatra, in welcoming the holy month of Ramadan. This tradition not only functions as a social and cultural activity, but also contains deep religious values. Mamogang is marked by the slaughter of livestock and the distribution of meat to the community, especially to those in need, as a form of gratitude and social concern. This tradition reflects the integration of Islamic values ​​and local Batak culture, which has been going on since the early Islamization process in the coastal areas of West Sumatra. The implementation of  mamogang also involves self-purification rituals such as Balimo-limo which strengthen the spiritual aspect before fasting. However, modernization and the decreasing participation of the younger generation are challenges in its preservation. This article uses a qualitative approach through literature study to explore the meaning, history, and efforts to preserve Mamogang as a symbol of cultural resistance and a means of character education based on Islamic values. The Mamogang tradition not only strengthens cultural identity, but also becomes a spiritual reflection in welcoming the blessed month of Ramadan.